Respuesta :
For this case we have that by definition, the roots, or also called zeros, of the quadratic function are those values of x for which the expression is 0.
Then, we must find the roots of:
[tex]2x ^ 2-4x + 5 = 0[/tex]
Where:
[tex]a = 2\\b = -4\\c = 5[/tex]
We have to:[tex]x = \frac {-b \pm \sqrt {b ^ 2-4 (a) (c)}} {2 (a)}[/tex]
Substituting we have:
[tex]x = \frac {- (- 4) \pm \sqrt {(- 4) ^ 2-4 (2) (5)}} {2 (2)}\\x = \frac {4 \pm \sqrt {16-40}} {4}\\x = \frac {4 \pm \sqrt {-24}} {4}[/tex]
By definition we have to:
[tex]i ^ 2 = -1[/tex]
So:
[tex]x = \frac {4 \pm \sqrt {24i ^ 2}} {4}\\x = \frac {4 \pm i \sqrt {24}} {4}\\x = \frac {4 \pm i \sqrt {2 ^ 2 * 6}} {4}\\x = \frac {4 \pm 2i \sqrt {6}} {4}\\x = \frac {2 \pm i \sqrt {6}} {2}[/tex]
Thus, we have two roots:
[tex]x_ {1} = \frac {2 + i \sqrt {6}} {2}\\x_ {2} = \frac {2-i \sqrt {6}} {2}[/tex]
Answer:
[tex]x_ {1} = \frac {2 + i \sqrt {6}} {2}\\x_ {2} = \frac {2-i \sqrt {6}} {2}[/tex]